An elastic–plastic model for porous rocks with two populations of voids. (June 2016) - Shen, W.Q.; Shao, J.F.
Abstract: In the present work, a new elastic–plastic model is proposed for a class of porous rock-like materials with two populations of pores at different scales. This model is based on the closed-form plastic criterion which was established from a nonlinear homogenization procedure in our previous work (Shen et al., 2014) . This criterion explicitly takes into account the effects of two populations of voids, respectively distributed at the microscopic and mesoscopic scales. In order to consider the plastic compressibility and pressure dependency, the solid phase at the microscopic scale is assumed to obey to a Drucker–Prager criterion. The constitutive model is completed by a non-associated plastic flow rule and an isotropic hardening law, which are defined in a phenomenological way. The proposed model is applied to describe the macroscopic mechanical behavior of the Lixhe chalk with different confining pressures. Comparisons between numerical results and experimental data are presented for the verification of the proposed model.